Taḥlīl Nuṣūṣ al-Qirā’ah Min Kitāb Ta`līm al-Lughah al-`Arabiyah Li aṣ-Ṣaf aṡ-Ṡāliṡ al-Mutawassiṭah Min Ḥaiṡ al-Lughah Wa aṡ-Ṡaqāfah al-Islāmiyyah `Alā al-Manhaj ad-Dirāsī 2013 - Muhammad Hanif Taufiq; Moch. Fajarul Falah; Zulhelmi Zulhelmi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
Overall, the goal of teaching Arabic at an intermediate level about religious ministry is to strengthen reading skills and increase religious knowledge. This is reflected in the planning of the Arabic subject at the intermediate level, so the reading texts must contain the two things mentioned, whether the application of the linguistic rules that have been studied or include religious knowledge in order to achieve the goal of teaching the Arabic language. The teaching and learning process needs the appropriate educational resources for the current curriculum. One of the educational resources is the textbook. The researcher found a book for teaching Arabic for the third intermediate grade, and this book is a model and was not printed for sale, so it can be fixed with suggestions and better analysis. According to this, the researcher analyzed the content of the book. This thesis aims to identify the compatibility of book-reading texts with the rules of arrangement and composing good study materials in terms of language and to identify the compatibility of book-reading texts with Islamic culture. The research tools used to obtain the desired data are observation and files. As for the results of this message, they are: 1). The reading texts found in the aforementioned book did not include the linguistic structure and this was not taken into account in every topic, 2). Of the five existing texts, four are texts that correspond to the Islamic culture or the teachings and creed of Islam, but one text needs to reform the content and the subject to conform to the established planning.